Preparation and characterization of sugar palm fibers - Salit, Mohd Sapuan; Ishak, Mohamad Ridzwan; Muthukumar, Chandrasekar; Latiff, M. A. S.; Ya'acob, A. M.; Mazlan, Norkhairunnisa; Shahroze, Rao M. (CRC Press, 2019)
Various natural products from the sugar palm tree have been in use in Malaysia for hundreds of years. Sugar palm fiber, known as black fiber, is obtained from the sugar palm tree and can be used as reinforcement in composites. Sugar palm fibers are available in ready-to-use form and do not require secondary processing. Fibers can also be obtained from the frond, the bunch, and the trunk, with the main source being the hairy fiber, locally called ijuk, which wraps around the trunk. In this chapter, we review the mechanical, physical, chemical, thermal and moisture absorption properties of the sugar palm fibers studied by various researchers.